1984
DOI: 10.1128/aem.48.3.491-496.1984
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and pathways of aniline elimination from aquatic environments

Abstract: The fate of aniline, a representative of arylamine pollutants derived from the manufacture of dyes, coal liquefaction, and pesticide degradation, was comprehensively evaluated by use of unpolluted and polluted pond water as model environments. Evaporation plus autoxidation proved to be minor elimination mechanisms, removing ca. 1% of the added aniline per day. Instantaneous binding to humic components of a 0. 1 % sewage sludge inoculum removed 4%. Biodegradation of aniline in pond water was accelerated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(54 citation statements)
references
References 30 publications
3
50
0
1
Order By: Relevance
“…The absence of other products from the samples, as well as the fact that aniline-grown isolates could oxidize the respective catechols (catechol, 4-chlorocatechol, 4-methylcatechol, and 3-nitrocatechol) without a lag, suggests that catechols are intermediates in the metabolism of anilines. Other re- searchers (11,15,28,31,34) have reported catechol and 4-chlorocatechol as metabolites of bacterial transformation of aniline and 3-chloroaniline. No reports on metabolites of bacterial degradation of the other five anilines were found.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of other products from the samples, as well as the fact that aniline-grown isolates could oxidize the respective catechols (catechol, 4-chlorocatechol, 4-methylcatechol, and 3-nitrocatechol) without a lag, suggests that catechols are intermediates in the metabolism of anilines. Other re- searchers (11,15,28,31,34) have reported catechol and 4-chlorocatechol as metabolites of bacterial transformation of aniline and 3-chloroaniline. No reports on metabolites of bacterial degradation of the other five anilines were found.…”
Section: Resultsmentioning
confidence: 99%
“…Biodegradation by bacteria, however, has been found to be the most significant mechanism of aniline removal from aquatic environments. Thus, Lyons et al (1984) found higher aniline biodegradation activity in polluted pond water than in unpolluted water.…”
Section: Discussionmentioning
confidence: 85%
“…However, these processes are much slower than biodegradation (Zissi and Lyberatos, 1999). Aromatic hydrocarbons are typically oxidized by dioxygenases to catechols, which are further cleaved (Atlas, 1997;Lyons et al, 1984;Peres et al, 1998;Pitter and Chudoba, 1990) and degraded through a tricarboxylic acid cycle to yield carbon dioxide as the end product.…”
Section: Introductionmentioning
confidence: 99%